2015
DOI: 10.1097/jom.0000000000000373
|View full text |Cite
|
Sign up to set email alerts
|

HRCT/CT and Associated Spirometric Effects of Low Libby Amphibole Asbestos Exposure

Abstract: Exposure to vermiculite containing amphibole fibers is associated with pleural and parenchymal HRCT/CT changes at low cumulative fiber exposure; these changes are associated with spirometric decrements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 27 publications
2
23
1
Order By: Relevance
“…Rohs et al (2008) found that pleural plaques (detected by CXR) were strongly dependent upon cumulative exposure for LAA, which is more in accord with expectation. More recently Lockey et al (2015) used HRCT/CT in a similar analysis of LAA and found that pleural changes (including both localized and diffuse pleural thickening) increased with cumulative exposure and employment duration.…”
Section: Dose-or Exposure-response and Pleural Plaquesmentioning
confidence: 99%
See 3 more Smart Citations
“…Rohs et al (2008) found that pleural plaques (detected by CXR) were strongly dependent upon cumulative exposure for LAA, which is more in accord with expectation. More recently Lockey et al (2015) used HRCT/CT in a similar analysis of LAA and found that pleural changes (including both localized and diffuse pleural thickening) increased with cumulative exposure and employment duration.…”
Section: Dose-or Exposure-response and Pleural Plaquesmentioning
confidence: 99%
“…These investigators concluded that the weight of evidence indicated that pleural plaques do not have clinically significant impacts on lung function and that the observed association is most likely due to unidentified pleural thickening or other factors. Lockey et al (2015) recently reported results of a careful study of workers employed at a plant that expanded Libby Vermiculite contaminated with LAA in Marysville, Ohio. They identified pleural plaques in the cohort using HRCT/CT and also measured FVC and FEV 1 values.…”
Section: Pleural Plaques and Impairments To Lung Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Lockey et al. ). In the amphibole‐exposed population of Libby MT, where exposures occurred due to the mining of asbestos‐contaminated vermiculite, pleural fibrosis is the predominant cause of morbidity and mortality (Peipins et al.…”
Section: Introductionmentioning
confidence: 97%